Study of the role of IQ in children with Enterobius vermicularis infestation compared to healthy children - Soudabeh Etemadi; Hosniehoseini (Open Journal of Pediatrics and Child Health - Peertechz Publications, 2021)
Background: Enterobius vermicularis has the widest geographic distribution among parasitic worms. This parasitic infestation is more common among children in population centers (nursery school, preschool). These parasites can affect the mental performance of children. This study investigated the role of IQ in children infestation with E.vermicularis were compared with healthy children in child care centers in Zahedan. Materials and methods: This descriptive study on 425 (218 boys- 207 girls) 3-10 years samples form three different geographical (North- south and center) were randomly selected. Scotch Tape Test was used to check for contamination with E.vermicularis. The Draw-a-Man test was used to study IQ in children. 30 children infestation with the parasite were selected as case group and 30 healthy children were selected as control group. Data were analyzed using SPSS software version 20 and pair sample T Test. Results: Prevalence of infestation was 7/5%. Average IQ scores in the control group was 106 and in patients' group was 104/5. The highest rate of infestation in children with average intelligence factor was 15(50%). Children with high IQ was the low rate of infestation 2 (6%) and showed no significant relation between 2 group in Average IQ scores (PV≥0.05=0.2). The highest rate of infestation was in the southern region (15 case). Conclusion: The mental performance of children in group control was improve and recommended affect cure E. vermicularis in mental performance of children.